(untitled) (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Gulo GS, Tumuyu SS, Patria MP. 2024. Sustainability strategy for turtle conservation in Kelapa Dua Island, Kepulauan Seribu District, Jakarta, Indonesia. Biodiversitas 25: 2307-2314. The background of this research stems from the excessive exploitation and shift from subsistence to commercial use that has caused a decline in turtle populations. Therefore, it is necessary to safeguard turtle populations within Indonesia’s distinct marine habitats, particularly at SPTN (National Park Management) I, Kelapa Dua Island, Kepulauan Seribu, Jakarta, Indonesia. Addressing the challenges in turtle conservation, this study systematically collected data through expert interviews, providing in-depth insights into the conservation landscape. The research methodology includes data collection via expert interviews and subsequent analysis using the Strengths, Weaknesses, Opportunities, and Threats (SWOT) method, providing a strategic framework to enhance conservation outcomes. The results highlight the critical need for habitat protection, stakeholder involvement, and rigorous law enforcement. Based on the four alternative strategies that have been prepared, the S-T strategy approach has the highest score, namely 4, making it a priority strategy for sustainable turtle conservation on Kelapa Dua Island. The following strategic priorities are W-O strategy, S-O strategy and W-T strategy. This study’s conclusion shows suitable strategies for research problems, such as advocation for habitat protection, active stakeholder involvement, and strict law enforcement to ensure the effectiveness and sustainability of conservation initiatives.